Shifting in Mindset of Local Community Towards MotoGP Race Event in Indonesia - Taufiq Kurniawan; Baiq Ade Septa Iswarindi; Linda Rahmiwati; Lóránt Dénes Dávid (PT FORMOSA CENDEKIA GLOBAL, 2023)
The international-class event of the MotoGP Mandalika held in Lombok, Indonesia, has succeeded in capturing the enthusiasm of people around the world. This event has become the most discussed issue throughout the year. As a result, the Mandalika Moto GP race event became a prestigious racing event that was able to make Indonesia's name went global. The total number of spectators reached 102,801 making it the event with largest number of spectators. From an economic standpoint, this surely delivers positive impact for the country in reviving tourism which was paralyzed due to the Covid-19 pandemic. In line with that, this study aims to determine the effect of the development of Mandalika International Circuit of MotoGP race event on the mindset change of the local community before and after the event is carried out. This research applies descriptive qualitative approach with the subjects used in the study are Local Community of Pujut Village, Lombok, Indonesia. The data collection techniques used are direct observation, interviews and documentation. The data analysis technique used in this study is a qualitative descriptive analysis of the interactive model. The results and discussions will be further discussed